Impacts of enzymes and probiotic in improving the utilization of sieved olive pulp meal in growing rabbit diets - A Alderey, Abd Alfattah; El Kassas, Nabila E M; Hussein, Eman A; Farag, Soha A; Hassan, Ayman A; Atia, Safaa E S; Gomaa, Manal H A; El Hadad, Eman S; Abu Hafsa, Salma H (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This research assesses the utilization of sieved olive pulp (SOP) in the diet of growing rabbits through the use of an exogenous enzyme or dry yeast as a pretreatment. Materials and Methods: One hundred sixty-eight male V-Line rabbits aged 5 weeks (weighing 550 ± 25 gm) were randomly divided into seven groups with eight replicates each as follows: the control group was fed a basal diet without supplementation; while the other six groups were fed basal diets containing 20% and 25% of SOP and supplemented with 0.1 gm/kg Econase (E), 0.5 gm/kg dry yeast (Y), and a combination of both. The experiment lasted for 8 weeks. Results: The results indicated that supplementation of E, Y, and EY into rabbit diets containing SOP improved live body weight, body weight gain, feed conversion ratio, and nutrient digestibility. A higher dressing percentage was observed in the groups fed a 20% and 25% SOP diet supplemented with EY (p < 0.05). The treated groups showed an increase in total protein, albumin, globulin, A/G ratio, total antioxidant capacity, superoxide dismutase, and glutathione peroxidase (p < 0.05), while there was a significant decrease in triglycerides, total cholesterol, and malondialdehyde levels (p < 0.05) compared to the control. Rabbit groups fed an SOP diet supplemented with E, Y, or EY demonstrated higher (p < 0.05) economic efficiency compared to the control. Conclusion: Supplementing the diet of rabbits containing SOP with exogenous enzymes and/or dry yeast enhances the nutritional value of SOP while improving rabbit performance, nutrient digestibility, and antioxidant status. Adv. Vet. Anim. Res., 11(1): 161-170, March 2024 http://doi.org/10.5455/javar.2024.k761